2006
DOI: 10.1590/s1678-77572006000600002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatments on the spreading velocity of simplified adhesive systems

Abstract: Objectives:To determine the roughness of glass surfaces submitted to different treatments and to correlate it with the spreading velocity of two adhesive systems.Materials and Methods:Glass slides were used as substrates to evaluate the spreading velocity of Single Bond and Prime & Bond NT adhesive systems. Six different surface treatments were compared: 1) no treatment; 2) silanization (SL); 3) sandblasting (SB); 4) SB + SL; 5) 10% hydrofluoric acid treatment (HF); 6) HF + SL. Before and after treatments, sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Additionally, air abrasion removes the possible impurities, such as: oil, unfavorable oxides, smear product, and other contaminants, from the surface to improve cement wettability specially when proceeded with priming procedure (Gargari et al, 2010, Haneda et al, 2009, Pazinatto et al, 2006, Rodríguez et al, 2010, Yucel et al, 2018). Freitas and Francisconi (2004) showed that air abrasion group with 100 µm aluminum oxide presented the highest values of bond strength, while the group that had no surface treatment presented low values.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, air abrasion removes the possible impurities, such as: oil, unfavorable oxides, smear product, and other contaminants, from the surface to improve cement wettability specially when proceeded with priming procedure (Gargari et al, 2010, Haneda et al, 2009, Pazinatto et al, 2006, Rodríguez et al, 2010, Yucel et al, 2018). Freitas and Francisconi (2004) showed that air abrasion group with 100 µm aluminum oxide presented the highest values of bond strength, while the group that had no surface treatment presented low values.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical or chemical surface treatments promote an increase in the porosity and roughness of dental ceramics, improving wettability 36,37) . Rougher surfaces have wider contact areas available for bonding, and also provide for an increased surface free energy in comparison to flatter or smoother surfaces 34,35) .…”
Section: Discussionmentioning
confidence: 99%
“…The removal of collagen results in dentin surface similar to those of etched enamel ( 17 ). Rougher surfaces have wider contact areas available for bonding, and also provide an increased surface free energy in comparison to flatter or smoother ones ( 24 ).…”
Section: Discussionmentioning
confidence: 99%